Synthesis, crystal structure, magnetic properties and Hirshfeld surface analysis of two cobalt(II) complex anions templated by pyridinium-based cations. (1st March 2023) - Njiki, Line D.D.; Ndosiri, Bridget N.; Nana, Augustin N.; Bouraima, Adam; Pouamo, Ledoux S.; Capet, Frédéric; Foulon, Michel; Nenwa, Justin
Graphical abstract: Two bis(oxalato)cobaltate(II) complexes have been isolated and their magnetic behaviors investigated. Highlights: Two bis(oxalato)cobaltate(II) complexes have been obtained through careful metathesis reactions. The counter cations significantly influence the crystal structures. Experimental PXRD patterns are in agreement with simulations, thus confirming the phase purity. Structural cohesion is mainly established by hydrogen bonding and π–π stacking interactions. At low temperatures, Salts 1 and 2 show antiferromagnetic and paramagnetic behaviors, respectively. Abstract: Two organic–inorganic hybrid salts, (C6 H9 N2 )2 [Co(C2 O4 )2 ]·H2 O (1 ) and (C5 H7 N2 )2 [Co(C2 O4 )2 (H2 O)2 ] (2 ) (C6 H9 N2 + = 2-amino-3-methylpyridinium; C5 H7 N2 + = 4-aminopyridinium) have been obtained. Salt 1 is characterized by the formation of one-dimensional chains of the anionic complexes [Co(C2 O4 )2 ] 2-, with the Co(II) centers located in a distorted (2 + 2 + 2) octahedral environment of six oxygen atoms from three chelating oxalato(2 − ) ligands. By contrast, salt 2 features discrete anionic complexes [Co(C2 O4 )2 (H2 O)2 ] 2- with distorted (4 + 2) octahedral CoO6 coordination sphere formed by two bidentate O, O-donor oxalato(2 − ) ligands in the equatorial plane and two aqua ligands in the axial positions. Hydrogen bonding interactions of the type OH∙∙∙O and NH∙∙∙O along with π–π stacking interactions between pyridine rings contribute to the stabilization of the 3-D supramolecular frameworks in 1 and 2 . Temperature-dependence magnetic moment ( µ ) collected under zero-field cooled (ZFC) and field-cooled (FC) conditions revealed strong antiferromagnetic ordering below T N = 25 K for 1, a behavior which is confirmed by the negative Weiss constant, θ = − 27.6 K. By contrast, in 2, the Weiss constant, θ = 0 K is in line with a paramagnetic behavior. The three-dimensional Hirshfeld surface (3D-HS) analysis and the two-dimensional fingerprint plots (2D-FP) revealed that in 2, the structure is dominated by H∙∙∙O/ H∙∙∙O and H∙∙∙H contacts.